KINERJA KARYAWAN DITINJAU DARI ASPEK MOTIVASI DAN LINGKUNGAN KERJA - Norhayati (Faculty of Islamic Economics and Business, 2021)
This study aims to determine and analyze the effect of motivation and compensation on employee performance in CV Sari Sofa Lumajang. The design of this research is explanatory research. The data analysis used is Multiple Linear Regression Analysis. The results of this research showed that motivation has a positive effect on employee performance. Compensation has a positive effect on employee performance. Keywords: Motivation ; Compensation ; Employee Performance